2020
DOI: 10.3389/fphys.2020.00450
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Exercise Training During Pregnancy to Improve Maternal Vascular Health: Focus on Gestational Hypertensive Disorders

Abstract: Hypertensive disorders of pregnancy, including gestational hypertension and preeclampsia, occur in up to 10% of pregnancies and are associated with increased lifelong cardiovascular risk. Physical activity improves cardiovascular health in pregnancy and may lower the risk of developing hypertensive disorders of pregnancy. However, a minority of pregnant women comply with the recommended level of physical activity. Adequate knowledge on the physiological effects of exercise in healthy pregnancy could help to ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
6

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 91 publications
0
18
0
6
Order By: Relevance
“…Em longo prazo, cerca de 50% dessas mulheres desenvolvem diabetes melito (DM) tipo 2 e os seus filhos correm risco maior de nascer pós-termo, bem como são mais propensos a desenvolver síndrome metabólica na infância e na vida adulta. [53][54][55] Modificações de estilo de vida como dieta e exercícios são a base para o tratamento do DMG e importantes aliadas quando associadas ao tratamento medicamentoso. Em contrapartida, os estudos mostram que o comportamento sedentário aumenta o risco de DMG.…”
Section: Diabetes Melitounclassified
See 2 more Smart Citations
“…Em longo prazo, cerca de 50% dessas mulheres desenvolvem diabetes melito (DM) tipo 2 e os seus filhos correm risco maior de nascer pós-termo, bem como são mais propensos a desenvolver síndrome metabólica na infância e na vida adulta. [53][54][55] Modificações de estilo de vida como dieta e exercícios são a base para o tratamento do DMG e importantes aliadas quando associadas ao tratamento medicamentoso. Em contrapartida, os estudos mostram que o comportamento sedentário aumenta o risco de DMG.…”
Section: Diabetes Melitounclassified
“…Em contrapartida, os estudos mostram que o comportamento sedentário aumenta o risco de DMG. 53,56 Nos casos de DMG, os estudos têm demonstrado evidências de que os exercícios orientados reduzem possíveis desfechos negativos maternos e fetais. No entanto, nas gestantes com DM preexistente, tal evidência ainda não foi comprovada.…”
Section: Diabetes Melitounclassified
See 1 more Smart Citation
“…A 2020 randomized controlled trial (RCT), showed 4 months of regular exercise training for patients with heart related issues had a positive effect on the peripheral autonomic function and hypertension [16]. Another 2020 reviewconfirmed the positive effects of exercise training on hypertension and highlighted the importance of attention to patient safety during exercise performance [17].…”
Section: Effect Of Exercise Training On Cardiovascular Risk Factorsmentioning
confidence: 99%
“…ACOG has also recommended moderate physical activities for 150 minutes a week or moderate physical activities for 30 minutes on most weekdays for all women lacking midwifery or medical problems and complications [11] . There is remarkable evidence confirming that conducting physical activity during pregnancy is associated with reduced diabetes [12] , reducedpretermdelivery [13] , preserving and improving the cardiovascular activities, fitness, physical vigor, and reduced back pain and sciatica [14] , reduced risk of suffering from preeclampsia [15] , improved sleep during pregnancy [1] , reduced depression during pregnancy and later [16] , reduced urinary problems [17] , and improved quality of life [18] .In addition to the aforementioned benefits, various studies have indicated that fetal heart rate as well as fetal birth weight are not influenced by harmful effects in healthy mothers who conduct moderate physical activities [19] ; during and after the physical activities, the fetal heart rate increases by 10 to 30 rate in comparison to the basic heart rate [20] . The maternal physical activity level is inversely related to the fetal weight; in pregnancies associated with moderate physical activities, the fetus enjoys a normal weight.…”
Section: Introductionmentioning
confidence: 99%